Analysis of Man-Made Risks: The Indian Context - Saha, Bhola (Journal of Advanced Research in Alternative Energy, Environment and Ecology; Vol 3 No 3&4 (2016): Journal of Advanced Research in Alternative Energy, Environment and Ecology, 2021)
Risk is the probability of any harmful consequences from the occurrence of any event that disrupts the functioning of a certain region. In India, a lot of research work and development has been made in the field of risk reduction due to natural events but not much of comprehensive work has been done for risk reduction due to man-made events. The article consists of two parts: the first part is a data compilation on life losses due to man-made reasons and shows us why research work and development in the field of risk reduction due to man-made events in India is required. The second part consists of a suggestive methodology to develop framework that can be used for assessing man-made risks in India.